Ultrafast Strong-Field Tunneling Emission in Graphene Nanogaps - Son, Byung Hee; Kim, Hawn Sik; Park, Ji Yong; Lee, Soonil; Park, Doo Jae; Ahn, Yeong Hwan (ACS Photonics, 2018)
We demonstrate subcycle electron pulse generation in a nanogap of graphene when irradiated by a femtosecond laser pulse in the near-infrared region (800 nm). A strong photoinduced emission was produced when the gap area was irradiated by the ultrashort pulse laser. The graphene, which has atomically sharp edges with a large damage threshold, enables us to achieve a strong tunneling regime for the subcycle field emission. The photoinduced signals exhibited an anomalous increase in nonlinear order as a function of incident pulse energy in the presence of static electric field. A dynamical analysis of tunneling electrons based on the semiclassical model, which considers the contribution from the recoil electrons, reproduced our observation successfully. The large field enhancement near the graphene edge enabled us to reach the deep tunneling regime with the extraordinary Keldysh parameter of 0.2 in the near-infrared region, which has not been accessible by conventional metal nanostructures.
Keywords: Attoseconds; Incident pulse energy; Keldysh parameter; Near infrared region; Photoinduced emission; Static electric fields; Strong field; Sub-cycle; attosecond; graphene; Keldysh parameter; strong-field photoemission; subcycle wavepacket